GALNT14 genotype effectively predicts the therapeutic response in unresectable hepatocellular carcinoma treated with transcatheter arterial chemoembolization. (March 2016) - Liang, Kung-Hao; Lin, Chih-Lang; Chen, Sung-Fang; Chiu, Chih-Wei; Yang, Pei-Ching; Chang, Ming-Ling; Lin, Chen-Chun; Sung, Kai-Feng; Yeh, Cassandra; Hung, Chien-Fu; Chien, Rong-Nan; Yeh, Chau-Ting
Aim: Transcatheter arterial chemoembolization is currently the standard treatment in hepatocellular carcinoma patients with Barcelona Clinic Liver Cancer stage B. Genomic variants of GALNT14 were recently identified as effective predictors for chemotherapy responses in Barcelona Clinic Liver Cancer stage C patients.Methods: We investigated the prognosis predictive value of GALNT14 genotypes in 327 hepatocelluar carcinoma patients treated by transcatheter arterial chemoembolization.Result: Cox proportional hazards model analysis showed that the genotype 'TT' was associated with shorter time-to-response (multivariate p < 0.001), time-to-complete-response (p = 0.004) and longer time-to-tumor progression (p < 0.001), compared with the genotype 'non-TT'. In patients with albumin <3.5 g/dl, genotype 'TT' was associated with longer overall survival (p = 0.027). Finally, genotype 'TT' correlated with higher cancer-to-noncancer ratios of GALNT14 protein levels, lower cancer-to-noncancer ratios of antiapoptotic cFLIP-S, and a clustered glycosylation pattern in the extracellular domain of death receptor 5.Conclusion: GALNT14 genotypes were significantly associated with clinical outcomes of transcatheter arterial chemoembolization. The differential status of extrinsic apoptotic signaling between cancerous and non-cancerous tissues might underlie the clinical association.